Transformation of Ministry from Within: The Integration of Theology and Spirituality in the Formation of Specialised Church Ministers - Saghoa, Akwilla; Mawikere, Marde Christian Stenly; Rampengan, Priscila Feibe (International Journal of Education, Information Technology, and Others, 2025)
The ministry of specialised servants within the dynamic context of the contemporary church faces significant challenges, ranging from spiritual fatigue and psychological pressure to a crisis of meaning in fulfilling their calling. This phenomenon demands an approach that is not solely structural or technical but also addresses the deepest dimensions of ministry, namely theology and spirituality. This study aims to explore how the integration of profound theological understanding and consistent spiritual practice can restore and sustain specialised ministry from within. The method employed is a descriptive qualitative study, utilising library research and contextual theological reflection. The findings indicate that a holistic understanding of the nature of ministry in the light of Christ’s redemptive work, combined with spiritual disciplines such as prayer, meditation on Scripture, fasting, and silence, constitutes an essential foundation for building spiritual resilience and ministerial integrity. Formation that integrates theological and spiritual aspects has been shown to foster renewed motivation, strengthen commitment, and produce authentic and transformative ministry. Thus, the restoration of ministry from within is an ongoing process requiring personal awareness, communal support, and a church ecosystem that nurtures spiritual life holistically and contextually.